Pasture’s Role in Climate Change Mitigation - Maria Silveira; Rosvel Bracho; Curtis Dell; Abmael Cardoso (EDIS)
This new 4-page publication of the UF/IFAS Department of Soil, Water, and Ecosystem Sciences provides information about the role of native and cultivated pastures in climate change mitigation and the opportunities and challenges for improving carbon sequestration in agroecosystems. Climate change mitigation in the context of this publication refers to actions that reduce the rate of climate change. This information should be of interest to stakeholders, students, scientists, and environmental agencies interested in enhancing ecosystems services provided by grazing lands. Written by Maria Silveira, Rosvel Bracho, Curtis Dell, and Abmael Cardoso. https://edis.ifas.ufl.edu/ss708